Sites of contestation in global fur networks. Issue 108 (January 2020) - Kleibert, Jana M.; Hess, Martin; Müller, Felix C.
Highlights: GPNs of fur are subject to multi-sited and antagonistic contestations. Investigates contestation at production, circulation, regulation and consumption sites. Reveals circulation as underutilised sites of contestation. Shows material and discursive dimensions in struggles over "ethical" GPNs. Abstract: Fur is a highly contested commodity, yet constitutes a growing global market. Global production networks (GPNs) of fur are premised upon the commodification of nature in the form of animal skins, which is contested by consumers and civil society groups such as animal rights activists. While there is already a considerable body of work on ethical consumption and environmental governance in/of GPNs, we argue that the strategies of political contestation by producers and consumers alike deserve more explicit attention. In particular, the ways in which various GPN actors struggle over valuation requires attention to the multiplicity of sites of contestation. We investigate sites of contestation that span the global geographies of fur production, regulation, circulation and consumption. Our analysis is based on qualitative research at fur farms, auctions, trade fairs, design centres, whole-sale and retail spaces in several countries. By shedding light on the political-economic, discursive and material dimensions of contestation we aim to contribute to a cultural political economy of GPNs.